Interaction of functionalized graphene with cellular membranes: an in silico investigation of graphene-based nanovehicle toward biomedical applications - Gholami, Maryam; Zaboli, Ameneh; Hashemzadeh, Hassan; Shirshahi, Vahid (Frontiers in Nanotechnology, 2024)
Nanomaterials, especially graphene derivatives, have become major tools in the biomedical area. Understanding the way that graphene interacts with component elements of biological systems, like biological membranes, is critical for the development of successful biomedical applications. The interaction mechanism of graphene sheets with a model cell membrane was investigated in this study using molecular dynamics (MD) simulations under three different conditions: pristine graphene (PG), carboxyl group-functionalized graphene (G-COOH), and amine group-functionalized graphene (G-NH2). The MD simulations demonstrated that functional groups on graphene surfaces improve their interaction with the head groups of the membrane. In 200 nanoseconds, PG reached equilibrium outside and near the phospholipid membrane. G-NH2 was positioned away from the model membrane's surface, while G-COOH and G-NH2 also achieved equilibrium outside the membrane. It was